REFLEKSI SRATEGI PERJUANGAN ARUNG PALAKKA DALAM KONTEKS PERANG SEMESTA - Talik, Krisaldi Gusti Pratama; Joni Widjayanto (PPM Sdirjianbang Akademi Militer, 2023)
The struggle of Arung Palakka in leading the people of Bone out of slavery in Makassar was one of the most historic events in Bone's independence. Arung Palakka who also was a nobleman of Bone was brought to Makassar to be used as a slave felt sorry to see his people suffering from forced labor carried out by Sultan Hasanuddin as the leader of the Makassar Kingdom. How the strategies and roles are carried out by Arung Palakka which are reflected in the context of the total war is the main purpose of this historical research. The method used in this study is a historical method that follows the flow of heuristic steps, sources of criticism, interpretation, and historiography. Based on the analysis conducted, it can be proven that in his efforts to bring the people of Bone out of slavery in Makassar, Arung Palakka collaborated with several kingdoms and even with VOC to succeed in providing strong resistance to Makassar and gaining victory.